Drone-based 3D High-resolution Imagery for Barrier Island in Nakdong River Estuary - Sung-Hwan Park; Nam-Hoon Kim; Jun-Yong Park; Eui-Young Jeong (Geo Data)
This study explores the use of drone-based photogrammetry to analyze the 3D topographic changes on Doyodeung, one of the barrier islands in the Nakdong River estuary. These islands act as natural buffers against wave energy from typhoons, providing essential habitats for migratory birds, while being highly dynamic and subject to morphological changes due to both natural processes and human activities. From June 2016 to July 2017, four drone surveys were conducted using the eBee fixed-wing drone, capturing high-resolution imagery of Doyodeung. The photogrammetry workflow involved aligning images, matching them with ground control points, and generating a detailed digital surface model and orthophotos with a high resolution of less than a few centimeters. The results demonstrated topographic changes, particularly after Typhoon Chaba in October 2016, which caused significant erosion along the shoreline. Following the typhoon, Doyodeung’s total area decreased by 2.5%, and its volume shrank by 8.8%. Despite some recovery observed in later months, the island’s geomorphology continued to evolve. This highresolution dataset provides crucial insights into geomorphological changes, coastal management, spatial variation of halophytes and marine environment monitoring, highlighting the effectiveness of drone-based techniques in capturing precise 3D data in dynamic, hard-to-reach environments.